PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP CHARACTER BUILDING SISWA MADRASAH IBTIDAIYAH - mohammad zakki (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
The purpose of this study was to determine the impact of social media on the character formation of MI students. Darul Hikmah Lebbek Pakong Pamekasan. the method in this study is a qualitative descriptive method through observation, interviews and documentation. while the results of this study are social media is very influential on students in character building, educational institutions always cooperate with families and communities in maintaining and limiting the use of social media in students, and the family environment must create independent education by setting good examples and supervising children in the use of social media.